2021
DOI: 10.1136/bmj.n2106
|View full text |Cite|
|
Sign up to set email alerts
|

Early computed tomography coronary angiography in patients with suspected acute coronary syndrome: randomised controlled trial

Abstract: Objectives To establish if the use of early computed tomography (CT) coronary angiography improves one year clinical outcomes in patients presenting to the emergency department with acute chest pain and at intermediate risk of acute coronary syndrome and subsequent clinical events. Design Randomised controlled trial. Setting 37 hospitals in the UK. Participants A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 30 publications
1
29
0
2
Order By: Relevance
“…Studies evaluating FFR-CT have shown inferior incremental diagnostic and prognostic value in comparison to functional testing [ 7 , 9 ]. Additionally, the recent FORECAST (Fractional Flow Reserve Derived From Computed Tomography Coronary Angiography in the Assessment and Management of Stable Chest Pain) trial of over 1400 patients, while referral to invasive angiography was lower, the use of FFR-CT did not demonstrate any benefits in terms of healthcare costs, cardiovascular outcomes, or quality of life compared to CT-alone [ 10 ]. Similarly, the recent RAPID-CT (Rapid Assessment of Potential Ischaemic Heart Disease with CTCA) trial [ 11 ] included 1748 patients with intermediate risk with suspected or a provisional diagnosis of acute coronary syndrome randomised to Early CCTA and standard of care compared with standard of care only.…”
Section: Disagreement With Some Aspects Of the Guidelinesmentioning
confidence: 99%
“…Studies evaluating FFR-CT have shown inferior incremental diagnostic and prognostic value in comparison to functional testing [ 7 , 9 ]. Additionally, the recent FORECAST (Fractional Flow Reserve Derived From Computed Tomography Coronary Angiography in the Assessment and Management of Stable Chest Pain) trial of over 1400 patients, while referral to invasive angiography was lower, the use of FFR-CT did not demonstrate any benefits in terms of healthcare costs, cardiovascular outcomes, or quality of life compared to CT-alone [ 10 ]. Similarly, the recent RAPID-CT (Rapid Assessment of Potential Ischaemic Heart Disease with CTCA) trial [ 11 ] included 1748 patients with intermediate risk with suspected or a provisional diagnosis of acute coronary syndrome randomised to Early CCTA and standard of care compared with standard of care only.…”
Section: Disagreement With Some Aspects Of the Guidelinesmentioning
confidence: 99%
“…CCTA clearly provides high accuracy for detecting obstructive CAD, and the high NPV determines CCTA as an effective non-invasive imaging procedure to exclude significant CAD in all risk groups, including stable symptomatic patients and those with acute coronary syndrome (17)(18)(19)(20). A previous study showed that up to 80% of ICAs can be avoided for patients with a low prevalence of CAD, since CCTA can effectively determine the need for ICA (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The recent VERDICT (Very Early Versus Deferred Invasive Evaluation Using Computerized Tomography in Patients with Acute Coronary Syndromes) trial showed that although CCTA may effectively rule out obstructive disease in non‐ST elevation acute coronary syndrome, with a negative predictive value of 91% and sensitivity of 97%, the RAPID‐CTCA (Rapid Assessment of Potential Ischaemic Heart Disease with CTCA [CT Coronary Angiography]) trial found that early use of CCTA did not reduce death or subsequent MI in patients presenting with suspected acute coronary syndrome. 54 , 55 …”
Section: Role Of Coronary Computed Tomography Angiography In Minocamentioning
confidence: 99%